A construção das cidades: processos educativos em uma transformação urbana - Carneiro, Daniel Marostegan e (2008)
The cities building is interconnected to the logic of wealth s accumulation, guide of the capitalist society where we are in. In this way, the city comes up with segregated, divided and dominated spaces which do not allow good conditions for housings and urban infra-structure to a big quantity of people, giving new shapes and increasing the actual social inequality. This work understands the cities building as a complex relationship between a lot of social practices which interacts one to each other, sometimes more conflicting and sometimes less conflicting, and the study will be concentrated on the social practice urban transformations, carried through the public government, on regions occupied by low income s population . From the premise that on the social practices coexist educative process, through of what the participants of those practices learn and teach, this study looks to identify the educational process present on the social practice studied. The work characterize by it self as a qualitative research done from a case study, which configures as a urban area occupied by a low income s population, identified as Orfanato , located in the south area of São Carlos city, interior of São Paulo State. From the intervention of the municipal public government this occupation is being completely removed to a region in the other extreme of city, and what, besides the removal, contemplate the building of a housing state through the mutirão process that when putted families from some city s region together and under the municipal public government coordination, edify a new district. The removing process ends in an Orfanato's population dividing, where part of the population have engaged in the mutirão program and some have not. In the mentioned case, I demand to identify the educative process present in such urban transformation, with emphasis for those process that point to indicatives of inhabitant s autonomy of the Orfanato, meaning, conducting their own lives.